Developmental Treatment with Ethinyl Estradiol, but Not Bisphenol A, Causes Alterations in Sexually Dimorphic Behaviors in Male and Female Sprague Dawley Rats - Ferguson, Sherry A.; Law, Charles Delbert; Kissling, Grace E. (Toxicological sciences, 2014)
The developing central nervous system may be particularly sensitive to bisphenol A (BPA)-induced alterations. Here, pregnant Sprague Dawley rats (n = 11-12/group) were gavaged daily with vehicle, 2.5 or 25.0 μg/kg BPA, or 5.0 or 10.0 μg/kg ethinyl estradiol (EE2) on gestational days 6-21. The BPA doses were selected to be below the no-observed-adverse-effect level (NOAEL) of 5 mg/kg/day. On postnatal days 1-21, all offspring/litter were orally treated with the same dose. A naïve control group was not gavaged. Body weight, pubertal age, estrous cyclicity, and adult serum hormone levels were measured. Adolescent play, running wheel activity, flavored solution intake, female sex behavior, and manually elicited lordosis were assessed. No significant differences existed between the vehicle and naïve control groups. Vehicle controls exhibited significant sexual dimorphism for most behaviors, indicating these evaluations were sensitive to sex differences. However, only EE2 treatment caused significant effects. Relative to female controls, EE2-treated females were heavier, exhibited delayed vaginal opening, aberrant estrous cyclicity, increased play behavior, decreased running wheel activity, and increased aggression toward the stimulus male during sexual behavior assessments. Relative to male controls, EE2-treated males were older at testes descent and preputial separation and had lower testosterone levels. These results suggest EE2-induced masculinization/defeminization of females and are consistent with increased volume of the sexually dimorphic nucleus of the preoptic area (SDN-POA) at weaning in female siblings of these subjects (He, Z., Paule, M. G. and Ferguson, S. A. (2012) Low oral doses of bisphenol A increase volume of the sexually dimorphic nucleus of the preoptic area in male, but not female, rats at postnatal day 21. Neurotoxicol. Teratol. 34, 331-337). Although EE2 treatment caused pubertal delays and decreased testosterone levels in males, their behaviors were within the range of control males. Conversely, BPA treatment did not alter any measured endpoint. Similar to our previous reports (Ferguson, S. A., Law, C. D. Jr and Abshire, J. S. (2011) Developmental treatment with bisphenol A or ethinyl estradiol causes few alterations on early preweaning measures. Toxicol. Sci. 124, 149-160; Ferguson, S. A., Law, C. D. and Abshire, J. S. (2012) Developmental treatment with bisphenol A causes few alterations on measures of postweaning activity and learning. Neurotoxicol. Teratol. 34, 598-606), the BPA doses and design used here produced few alterations.